2018
DOI: 10.1111/resp.13435
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive ventilation or high‐flow oxygen therapy: When to choose one over the other?

Abstract: It has been found that high-flow oxygen therapy (HFOT) can reduce mortality of patients admitted to intensive care unit (ICU) for de novo acute respiratory failure (ARF) as compared to non-invasive ventilation (NIV). HFOT might therefore be considered as a firstline strategy of oxygenation in these patients. The beneficial effects of HFOT may be explained by its good tolerance and by physiological characteristics including delivery of high FiO 2 , positive end expiratory pressure (PEEP) effect and continuous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 86 publications
0
19
0
1
Order By: Relevance
“…HFNC is a more comfortable means of respiratory support and is associated with more relief of dyspnea compared to conventional oxygen therapy, 16,40 and HFNC is frequently used in patients with hypoxemic respiratory failure with S pO 2 Ͻ 90 despite being treated with conventional oxygen therapy during postextubation respiratory failure and during intubation. 11 In contrast to the trial by Frat et al, 5 other trials found no difference between HFNC and conventional oxygen therapy in subjects with hypoxemic respiratory failure. 12,16,17,40,41 However, HFNC showed superiority over conventional oxygen therapy in subjects with postextubation respiratory failure in terms of a reduction of intubation rates.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…HFNC is a more comfortable means of respiratory support and is associated with more relief of dyspnea compared to conventional oxygen therapy, 16,40 and HFNC is frequently used in patients with hypoxemic respiratory failure with S pO 2 Ͻ 90 despite being treated with conventional oxygen therapy during postextubation respiratory failure and during intubation. 11 In contrast to the trial by Frat et al, 5 other trials found no difference between HFNC and conventional oxygen therapy in subjects with hypoxemic respiratory failure. 12,16,17,40,41 However, HFNC showed superiority over conventional oxygen therapy in subjects with postextubation respiratory failure in terms of a reduction of intubation rates.…”
Section: Discussionmentioning
confidence: 86%
“…9,10 Recently, high-flow nasal cannula (HFNC) therapy has been used more frequently in the treatment of acute hypoxemic respiratory failure. 11 In a large RCT, Frat et al 5 reported that HFNC was associated with a reduction in 90-d mortality when compared to NIV and conventional oxygen therapy in subjects with acute hypoxemic respiratory failure. However, further subsequent trials and metaanalyses showed no difference between HFNC and conventional oxygen therapy [12][13][14][15][16][17] or NIV.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the optimal treatment regimen for the management of moderate and severe bronchiolitis (SB) remains unclear. In recent years, heated humidified high‐flow nasal cannula (HHHFNC) therapy has been introduced as a novel alternative method for the management of acute respiratory distress due to bronchiolitis …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high-flow nasal cannula (HFNC), a non-invasive ventilation (NIV) modality, has become the preferred initial treatment method for children with respiratory distress. 5 The use of HFNC was previously limited to in neonatal intensive care units and pediatric intensive care units (PICU). 6 Given its proven safety and efficacy, it is currently used with increasing frequency in PEDs and general pediatric wards.…”
Section: Introductionmentioning
confidence: 99%